Comparison between the prevalence of iron deficiency anemia in children with urinary tract infections and without urinary tract infections in Hazrat Masoumeh Hospital of Qom in 2019-2020 - Razavi, Mohammad Reza; Akhavan Sepahi, Mohsen; Eshagh Hoseini, Kamal; Hamta, Amir; Shariatifar, Mohammad Ali (Journal of Pediatric Nephrology, 2022)
Background and Aim: Research into the association between anemia and urinary tract infections (UTIs) is not adequate and only a few studies are available in this regard. Therefore, the aim of this study was to investigate the relationship between iron deficiency anemia and urinary tract infections in children presenting to Hazrat Masoumeh Hospital, Qom, Iran. Methods: The medical records of pediatric patients with and without UTI hospitalized in Qom Hazrat Masoumeh Hospital were evaluated. Then, the anemia profile was evaluated in the two groups (e.g. hemoglobin, ferritin, transferrin, etc.) Results: There were 32 patients (64%) in the urinary tract infection group and 26 patients (52%) in the non-urinary tract infection group. Twenty-eight patients (56%) in the urinary tract infection group and 20 patients (40%) in the non-urinary tract infection group had iron deficiency anemia, but no significant relationship was found between the two groups (P value = 0.08). The mean hemoglobin concentration was 11.19 ± 1.73 in patients with urinary tract infection and 11.56 ± 1.89 in the non-infected group. Regarding anemia profile variables, no significant relationship was found between the two groups (P values: Hb = 0.15 SI = 0.21 TIBC = 0.90 Ferritin = 0.05 Transferrin sat = 0.132). Conclusion: No statistically significant difference was found in anemia between the two groups of children with and without urinary tract infections. However, the indicators of anemia were lower in children with urinary tract infections compared to the control group and these children are prone to anemia.